Optimising hospital management through integrated epidemiological data: A study in Samarinda - Ardan, M.; Febriyanto, Kresna (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: The high incidence of infectious diseases such as tuberculosis and dengue fever in Samarinda, coupled with the low integration of epidemiological data—only 47% of hospitals are connected to the Hospital Information System (SIRS), which impedes evidence-based decision-making and compromises hospital service quality.Objectives: This study aims to describe the integration of epidemiological data in hospital administrative management, to assess its impact on management effectiveness and service quality, and to examine the mediating roles of data quality, data utilisation, and administrative human resource capacity.Methods: A cross-sectional design was employed in 10 hospitals in Samarinda, involving 139 administrative staff selected through a purposive and convenience sampling. The data for this study were collected using a validated and reliable Likert-scale questionnaire (1–5) and were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) via Smart PLS.Results: Epidemiological Data Quality (β=0.979), Data Utilisation (β=0.273), and Administrative Human Resource Capacity (β=0.243) significantly influenced System Response to Outbreaks. All variables also significantly affected Hospital Administrative Management Effectiveness. System Response to Outbreaks mediated the relationship between organisational capabilities and administrative effectiveness (β=0.308), which subsequently had a significant impact on Hospital Service Quality (β=0.414).Conclusion: The quality of epidemiological data, its use in managerial decision-making, and the capacity of administrative personnel significantly influence the hospital service quality, both directly and through the mediating roles of system responsiveness and administrative management effectiveness.